EXPLORING COGNITIVE PROCESS OF RESEARCH TOPIC SELECTION IN ACADEMIC WRITING - Fahrus Zaman Fadhly; Emzir Emzir; Ninuk Lustyantie (English Review: Journal of English Education, 2018)
The purpose of this research is to explore and reconstruct the cognitive processes experienced by Indonesian scientific writers in selecting research topic in academic writing. By using grounded theory approach, this research explored the Indonesian scientific writers cognitive processes and revealed eleven ways or approaches in finding and selecting research topics, i.e: institutional research road map, literature review, search before research, research trends in the world, national topics of research, interpretation of regulations, court decisions, pros and cons of actual cases or topics, discussion and research sharing method, exposure of controlled data, and looking for possible space for existing papers. Each expertise background dicipline has its own ways and approaches in research topic selection, but there is red thread: the selection and determination of research topics rests on literature review. This research endorses practical approaches to find out research topics containing novelties and state of the art of the research in each discipline.Keywords: cognitive process; academic writing; research topic selection; Indonesian scientific writers; search before research.